2002
DOI: 10.1149/1.1483098
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylene oxide)-LiN(SO[sub 2]CF[sub 2]CF[sub 3])[sub 2] Polymer Electrolytes

Abstract: The present report describes the investigation performed on the interface established between lithium metal and poly(ethylene oxide) (PEO)-lithium bis(perfluoroethysulfonyl)imide (LiBETI), normalLiNfalse(SO2CF2CF3)2 polymer electrolytes. The studies were performed as a function of the polymer electrolyte salt concentration and temperature both in rest and in kinetic conditions by means of impedance measurements and galvanostatic tests, respectively. © 2002 The Electrochemical Society. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 14 publications
2
28
0
Order By: Relevance
“…24,25 The interfacial impedance of lithium metal and PEO (MW = 4000 kg/mol) with LiBETI was measured by Appetecchi, G. B. et al 26 They report a minimum of 80 cm 2 27 The values of R i reported in our study for LiFSI/PFE systems are thus similar to those of LiFSI/PEO, and significantly lower than that of LiTFSI/PEO. The interfacial resistances that were measured in the PEO electrolytes in References 26 and 27 were obtained without the passage of current.…”
Section: Resultssupporting
confidence: 69%
“…24,25 The interfacial impedance of lithium metal and PEO (MW = 4000 kg/mol) with LiBETI was measured by Appetecchi, G. B. et al 26 They report a minimum of 80 cm 2 27 The values of R i reported in our study for LiFSI/PFE systems are thus similar to those of LiFSI/PEO, and significantly lower than that of LiTFSI/PEO. The interfacial resistances that were measured in the PEO electrolytes in References 26 and 27 were obtained without the passage of current.…”
Section: Resultssupporting
confidence: 69%
“…This result is in a good agreement with previous reports which have indicated that there are no significant changes in the degree of ionic association resulting from the addition of inorganic fillers to polymer electrolytes [23][24][25]. In addition, the spectra agree with previously performed ionic conductivity [28,44] and pfg-NMR [45] measurements on solvent-cast and hot-pressed P(EO) 20 LiBETI polymer electrolyte containing SiO 2 (7 and 12 nm) and g-LiAlO 2 . The ionic conductivity of these electrolytes was shown to differ only slightly (see Table 1) and the Li + diffusion coefficient is essentially the same for the filler-free and 10 wt.% SiO 2 -P(EO) 20 LiBETI electrolytes, particularly at Tz80 8C.…”
Section: Effect Of Sio 2 and C-lialo 2 Fillers On Peosupporting
confidence: 92%
“…Scan rate: 0.5 mV s −1 . commonly observed in solvent-free polymer electrolytes [47][48][49], is due to the reaction between the lithium electrode and the polymer electrolyte to form a passive layer (SEI) [36] onto the lithium anode that protects the electrode from further reaction. At 40 • C the interfacial resistances decrease about one order of magnitude Table 3 Electrolyte bulk resistance (R b ), charge transfer resistance (Rct) and passive layer resistance (Rp) values for a PIL-LiTFSI-PYR14TFSI ternary polymer electrolyte (set C) in contact with a lithium anode at different storage times and temperatures.…”
Section: Interfacial Propertiesmentioning
confidence: 99%